Optimization of Production Processes in Micro, Small and Medium Metal Enterprises (SMEs Metal) using Fuzzy-Kano, QFD and SPC Methods: a Systematic Literature Review - Prihono; Febryanto, Indra Dwi; Utomo, Yitno (Tibuana, 2026)
Micro, Small, and Medium Enterprises (MSMEs), particularly in the metal industry, play a pivotal role in Indonesia’s economic development but face significant challenges in maintaining product quality, reducing defects, and responding to customer needs. This study conducts a Systematic Literature Review (SLR) to investigate the integration of Fuzzy-Kano, Quality Function Deployment (QFD), and Statistical Process Control (SPC) methods as a comprehensive approach for optimizing production processes in metal MSMEs. The literature was sourced from databases such as Scopus, Crossref, and Google Scholar, yielding 562 records, of which 35 relevant journal articles were analyzed in depth. Findings reveal that while QFD and SPC are frequently applied separately in MSMEs, research integrating these methods with Fuzzy-Kano remains limited. The review highlights that such integration offers substantial potential to improve product quality, align production with customer satisfaction, and enhance decision-making under uncertainty—ultimately supporting sustainable competitiveness. This study also identifies research gaps and proposes future directions, including the development of localized models tailored to SME contexts and the deeper integration of SPC within customer-oriented product development frameworks.